Al-Ďawāhir al-Tarkībiyyah fī al-Agniyyah "Taṣna' al-Mustaḥīl" lī Humood Al-Khuder - Fata, Khoirul; Wulandari, Dina Ayu (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This study deals with research in particular on tarkīb characteristics. The tarkīb has two main things, namely the subject and the backstop, and the field of this study is taken from the word "Taṣna' al-Mustaḥīl" of Humood Al-Khuder. This song was released on May 16, 2017, and is becoming more popular nowadays. This study is a desk study, and the technique of desk study is to collect data from written sources for data and linguistic context in the analysis. The main source is the word song makes the impossible. In this study, the researcher uses data analysis in the song "Tasna'ul Mustahil", an analysis of content (Analysis Content), which is one of the groups of analysis methods of linguistic text analysis. As a result of the study of synthesis characteristics in the song word "make the impossible", there are four types of tarkībs: tarkīb isnādi, tarkīb idāfi, tarkīb aṭfī, and tarkīb bayāni. There are 32 tarkīb in the song lyrics, meaning 16 tarkīb of the tarkīb isnādi, 9 tarkīb of the tarkīb idāfi, 7 tarkīb atfi, and one tarkīb of the graphic tarkīb. The most composite is the alloy tarkīb.